Tantangan Etika dan Pertimbangan Profesional dalam E-Konseling Berbasis Sekolah: Tinjauan Literatur Sistematis - Tyas Nurmaya Dewi (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The advancement of digital technology has encouraged the adoption of e-counseling as an integral component of guidance and counseling services in schools. While the use of digital-based services enhances accessibility and flexibility, it also presents various ethical challenges and professional demands for school counselors. This study aims to identify the ethical challenges associated with school-based e-counseling, analyze the professional considerations required of counselors, and examine the interrelationship among ethics, professionalism, and institutional support in the implementation of e-counseling services. The study employed a Systematic Literature Review (SLR) method guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework through a comprehensive search of articles indexed in Google Scholar, GARUDA, ERIC, Scopus, and ProQuest published between 2015 and 2025. The findings reveal that the primary challenges of e-counseling include data confidentiality, client privacy, digital information security, professional boundaries, and limitations in nonverbal communication. The results further indicate that digital competence, adherence to professional ethical standards, and institutional support from schools are critical factors influencing the effectiveness of e-counseling services. This study contributes a conceptual synthesis that positions ethics, counselors’ digital professionalism, and institutional governance as three interrelated pillars essential for the development of safe, ethical, and professional e-counseling practices within school settings.